Method for testing isotacticity of polyolefin material
By using nylon filters and Soxhlet extractors in the standard test of polyolefin materials, the test error problem caused by the filter paper moisture absorption is solved, and more efficient and accurate test results are achieved, meeting the strict demands of polyolefin materials in quality control and market applications.
Patent Information
- Application Number
- CN202510016079.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-18
AI Technical Summary
The existing polyolefin material isometric testing methods have inaccurate test results and large errors due to the strong moisture absorption ability of filter paper.
The dried polyolefin material is put into a nylon filter to tighten it to form a powder pack, and then extract it in a Soxhlet extractor. After the test is completed, the same-level calculation is calculated by drying until constant weight and difference subtraction.
This method improves the accuracy and efficiency of the test, reduces the error rate, and has extremely strong timeliness, can quickly feedback the test results and shorten the product evaluation cycle.
Smart Images

Figure BDA0005229963690000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of isotacticity testing, and in particular relates to a method for testing the isotacticity of a polyolefin material. Background Art
[0002] At present, polyolefin material consumption accounts for more than 60% of the national plastic consumption in the domestic plastic material consumption, and is the largest plastic variety in consumption. With the rapid development of polyolefin technology, its market share continues to increase, and the sustainable development of polyolefin technology has attracted widespread attention in the academic community. The quality of polyolefin materials determines the scope of application. Among the testing indicators of polyolefin materials, the isotacticity test is an important indicator. The level of isotacticity can reflect the crystallinity, melting point, tensile strength, impact strength and bending modulus of the material. Therefore, the test of isotacticity is particularly important.
[0003] At present, the test method for isotacticity is to use a Soxhlet extractor for testing. During the test, filter paper is used to cover the powder. However, the filter paper has a strong ability to absorb moisture, which has a significant impact on the test results. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a testing method for isotacticity of polyolefin materials, which is efficient, convenient and has a small testing error.
[0005] The present invention provides a method for testing the isotacticity of a polyolefin material, comprising the following steps:
[0006] Put the dried polyolefin material into a filter screen and tie it tightly to obtain a powder bag;
[0007] The powder bag is placed in a Soxhlet extractor for extraction. After the test is completed, the bag is dried to a constant weight, and the isotacticity is calculated by subtraction.
[0008] Preferably, the pores of the filter screen are 80 mesh, 100 mesh, 120 mesh, 200 mesh, 250 mesh, 300 mesh, 500 mesh, 600 mesh or 800 mesh.
[0009] Preferably, the polyolefin material is dried at a temperature of 60 to 90° C. for 1 to 8 hours.
[0010] Preferably, the extraction temperature is 100-150° C., and the number of extractions is 120-180 times.
[0011] Preferably, the filter screen is dried before use, and the drying temperature is 60 to 90° C. and the drying time is 1 to 8 hours.
[0012] Preferably, the subtraction method for isotacticity calculation includes:
[0013] Measure the total mass of the polyolefin material before extraction, recorded as M1;
[0014] After extraction and drying to constant weight, measure the mass of the polyolefin sample in the material bag and record it as M2;
[0015] The calculation formula of isotacticity is:
[0016] (M1-M2) / M1×100%.
[0017] Preferably, the polyolefin material to be determined does not need to be sieved;
[0018] There is no need to rinse the samples with acetone after testing.
[0019] Preferably, the size of the filter is (15-30) cm×(15-30) cm;
[0020] The shape of the filter is square or rectangular;
[0021] The width of the binding rope used for tightening is 1 to 3 cm and the length is 10 to 20 cm.
[0022] Preferably, the solvent used for extraction is selected from xylene, toluene or n-heptane.
[0023] Preferably, after taking out the sample, place it in an oven at 75±2°C, dry it for 4-8 hours, take out the powder and filter screen and place them in a dryer, take them out after cooling to room temperature, place them in an indoor environment for 15-30 minutes, weigh them, and record them as M2.
[0024] The present invention provides a method for testing the isotacticity of polyolefin materials, comprising the following steps: drying the polyolefin material and placing it in a filter screen, tying it up, and obtaining a powder bag; placing the powder bag in a Soxhlet extractor for extraction, drying the bag to a constant weight after the test is completed, and calculating the isotacticity by subtraction. Compared with traditional detection methods, the detection means described in the present invention has significant advantages in operation. Not only are the steps simple and clear, reducing the difficulty of operation, but the detection results are highly accurate, and the error rate is effectively reduced. At the same time, the detection method also has a strong timeliness, can quickly feedback the detection results, and greatly shortens the product evaluation cycle. Therefore, the present invention can fully meet the strict requirements of polyolefin materials in terms of quality control, product development and market application, and provides strong technical support for the product evaluation of polyolefin materials. DETAILED DESCRIPTION
[0025] The present invention provides a method for testing the isotacticity of a polyolefin material, comprising the following steps:
[0026] Put the dried polyolefin material into a filter screen and tie it tightly to obtain a powder bag;
[0027] The powder bag is placed in a Soxhlet extractor for extraction. After the test is completed, the bag is dried to a constant weight, and the isotacticity is calculated by subtraction.
[0028] The invention spreads the polyolefin material flatly in a clean glass surface dish, covers it with a plastic wrap, and pokes a plurality of pinholes to avoid the introduction of other dust and impurities, while ensuring that the moisture in the powder evaporates and escapes during the drying process.
[0029] After drying, the samples are crushed by a crusher. The polyolefin material samples to be tested do not need to be sieved.
[0030] In the present invention, the filter is preferably a nylon filter, more preferably one of 80 mesh, 100 mesh, 120 mesh, 200 mesh, 250 mesh, 300 mesh, 500 mesh, 600 mesh or 800 mesh nylon filter; a square or a rectangle of (15-30) cm*(15-30) cm*(15-30) cm in size is cut out, and a rope of 1-3 cm and a length of 10-20 cm is cut out accordingly, which is used to wrap the filter to prevent the powder from leaking out.
[0031] Specifically, the present invention preferably uses a 500-mesh nylon filter to cut out a square of about 15 cm×15 cm in size, and correspondingly cuts out a 1 cm, 15 cm long rope to wrap the filter to prevent the powder from leaking out.
[0032] The present invention preferably dries the powder and the filter screen; the polyolefin powder is dried at a temperature of 60 to 90°C for 1 to 8 hours; the filter screen is dried at a temperature of 60 to 90°C for 1 to 8 hours. Specifically, the treated powder and filter screen are placed in a 75°C oven, and after 6 hours, the powder and filter screen are taken out and placed in a dryer, and after cooling to room temperature, they are taken out and placed in an indoor environment for 15 minutes.
[0033] The present invention can improve the use efficiency of the Soxhlet extractor by introducing the filter screen treatment and can ensure that no other variables are introduced in the isotacticity test, ensure the authenticity and reliability of the data, and meet the testing requirements of various polyolefin materials. The nylon filter screen can be recycled.
[0034] The powder described in the present invention has static electricity, and it is preferred to use a deionizing fan to remove static electricity; then the material test package is made; the polypropylene sample is placed in a nylon filter and tied into a powder bag, which can test 5.0-6.0g of polyolefin samples for isotacticity at one time. Specifically, 5.0g of dry powder is weighed and placed in the filter, and tied with a rope to ensure that the filter does not leak after being wrapped. To ensure that the data is true and valid, prepare 2 powder bags of the same mass for testing. Accurately weigh the mass of the powder bag and record M1.
[0035] After obtaining the powder package, the present invention puts the powder package into a Soxhlet extractor for extraction. After the test is completed, the package is dried to a constant weight, and the isotacticity is calculated by difference subtraction.
[0036] The present invention selects a suitable solvent for solvent extraction, the test temperature is 100-150°C, and the number of extractions is 120-180 times. In the solvent extraction process, the selection of the solvent needs to be determined according to the type and characteristics of the polyolefin material to ensure that the non-isotactic part can be effectively extracted without damaging the isotactic part; the solvent includes one of xylene, toluene and n-heptane, and the specific selection needs to be comprehensively selected based on experimental conditions and sample characteristics.
[0037] The isotacticity calculation in the present invention adopts the difference subtraction method. First, the total mass of the polyolefin sample before extraction is measured, which is recorded as M1. Subsequently, after the Soxhlet extractor solvent extraction and drying, the mass of the polyolefin sample in the material bag is measured again, which is recorded as M2. The isotacticity calculation formula is: (M1-M2) / M1×100%, where (M1-M2) represents the mass of the soluble part, that is, the non-isotactic part. By calculating the percentage of this part in the total mass, the isotacticity of the polyolefin sample can be obtained.
[0038] There is no need to rinse the sample with acetone after the test.
[0039] The test method provided by the present invention can meet the isotacticity test requirements of various polyolefin materials. The method aims to significantly improve the isotacticity detection efficiency of polyolefin materials, including but not limited to important varieties such as polyethylene (PE), polypropylene (PP) and ethylene and alpha olefin copolymers.
[0040] Compared with traditional detection methods, the detection method described in the present invention has significant advantages in operation. Not only are the steps concise and clear, reducing the difficulty of operation, but also the detection results are highly accurate, effectively reducing the error rate. At the same time, the detection method also has a strong timeliness, can quickly feedback the test results, and greatly shorten the product evaluation cycle. Therefore, the present invention can fully meet the strict requirements of polyolefin materials in quality control, product development and market application, and provides strong technical support for the product evaluation of polyolefin materials.
[0041] The present invention puts the dried polyolefin material into a cleaned and dried filter screen, ties it with a cut rope to make a powder bag, puts the powder bag into a Soxhlet extractor for testing, dries the bag to a constant weight after the test, and calculates the isotacticity by difference subtraction.
[0042] In order to further illustrate the present invention, a method for testing the isotacticity of a polyolefin material provided by the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0043] Example 1
[0044] 1. Powder treatment: Choose self-produced HP550J polypropylene resin powder, take 25.0g, spread it flat on a clean glass surface dish, cover the kettle with plastic wrap, and poke multiple pinholes to avoid the introduction of other dust and impurities, while ensuring that the moisture in the powder evaporates during the drying process.
[0045] 2. Filter processing: Cut the 500-mesh nylon filter into a square of about 15cm*15cm, and cut out a 1cm, 15cm long rope to wrap the filter to prevent the powder from leaking out.
[0046] 3. Drying of powder and filter: Place the processed powder and filter in a 75℃ oven. After 6 hours, take out the powder and filter and place them in a dryer. After cooling to room temperature, take them out and place them in a indoor environment for 15 minutes.
[0047] 4. Preparation of material test package: Powder has static electricity, use deionizing fan to remove static electricity. Weigh 5.0g of dry powder and put it into the filter screen, tie it tightly with rope to ensure that the filter screen does not leak after wrapping. To ensure the authenticity and validity of the data, prepare 2 powder packages of the same quality for testing. Accurately weigh the mass of the powder package and record M1.
[0048] 5. Test: Place the powder bag in the extractor, add 150 mL of n-heptane, test temperature 110°C, extraction times 160±10 times, time 8 hours.
[0049] 6. Post-processing of material package: After the test, take out the sample, place it in a 75℃ oven, dry it for 8 hours, take out the powder and filter, place it in a dryer, cool it to room temperature, take it out, place it in a room for 15 minutes, weigh it and record the mass M2.
[0050] 7. Calculation: isotacticity of polyolefin materials.
[0051] Example 2
[0052] 1. Polyolefin material processing: Use self-produced HP550J polypropylene resin pellets, crush them with a high-speed crusher, take 25.0g, spread it flat on a clean glass surface dish, cover the kettle with plastic wrap, and poke multiple pinholes to avoid the introduction of other dust and impurities, while ensuring that the moisture in the powder evaporates during the drying process.
[0053] 2. Filter processing: Cut the 500-mesh nylon filter into a square of about 15cm*15cm, and cut out a 1cm, 15cm long rope to wrap the filter to prevent the powder from leaking out.
[0054] 3. Drying of powder and filter: Place the processed powder and filter in a 75℃ oven. After 6 hours, take out the powder and filter and place them in a dryer. After cooling to room temperature, take them out and place them in a indoor environment for 15 minutes.
[0055] 4. Preparation of material bags: Powders have static electricity, so use a deionizing fan to remove static electricity. Weigh 5.0g of dry powder and put it into the filter. Tie it up with a rope to ensure that the filter does not leak. To ensure that the data is true and valid, prepare two powder bags of the same quality for testing. Accurately weigh the weight of the powder bag and record M1.
[0056] 5. Test: Place the powder bag in the extractor, add 150 mL of n-heptane, test temperature 110°C, extraction times 160±10 times, time 8 hours.
[0057] 6. Post-processing of material package: After the test, take out the sample, place it in a 75℃ oven, dry it for 8 hours, take out the powder and filter, place it in a dryer, cool it to room temperature, take it out, place it in a room for 15 minutes, weigh it and record the mass M2.
[0058] Example 3
[0059] 1. Polyolefin material processing: Use self-produced HP550J polypropylene resin powder, take 25.0g, spread it flat on a clean glass surface dish, cover the kettle with plastic wrap, and poke multiple pinholes to avoid the introduction of other dust and impurities, while ensuring that the moisture in the powder evaporates during the drying process.
[0060] 2. Filter processing: Cut the 600-mesh nylon filter into a square of about 20cm*20cm, and cut out a 1cm, 15cm long rope to wrap the filter to prevent the powder from leaking out.
[0061] 3. Drying of powder and filter: Place the processed powder and filter in a 75℃ oven. After 4 hours, take out the powder and filter and place them in a dryer. After cooling to room temperature, take them out and place them in a indoor environment for 15 minutes.
[0062] 4. Preparation of material bags: Powders have static electricity, so use a deionizing fan to remove static electricity. Weigh 5.0g of dry powder and put it into the filter. Tie it up with a rope to ensure that the filter does not leak. To ensure that the data is true and valid, prepare two powder bags of the same quality for testing. Accurately weigh the weight of the powder bag and record M1.
[0063] 5. Test: Place the powder bag in the extractor, add 200 mL of n-heptane, test temperature 105°C, extraction times 130±10 times, time 6.5 hours.
[0064] 6. Post-processing of material package: After the test, take out the sample, place it in a 75℃ oven, dry it for 8 hours, take out the powder and filter, place it in a dryer, cool it to room temperature, take it out, place it in a room for 15 minutes, weigh it and record the mass M2.
[0065] 7. Calculation: Isotacticity of polyolefin materials
[0066] Example 4
[0067] 1. Polyolefin material processing: Use self-produced HP550J polypropylene resin pellets, crush them with a high-speed crusher, take 25.0g, spread it flat on a clean glass surface dish, cover the kettle with plastic wrap, and poke multiple pinholes to avoid the introduction of other dust and impurities, while ensuring that the moisture in the powder evaporates during the drying process.
[0068] 2. Filter processing: Cut the 500-mesh nylon filter into a square of about 15cm*15cm, and cut out a 1cm, 15cm long rope to wrap the filter to prevent the powder from leaking out.
[0069] 3. Drying of powder and filter: Place the processed powder and filter in a 75℃ oven. After 6 hours, take out the powder and filter and place them in a dryer. After cooling to room temperature, take them out and place them in a indoor environment for 15 minutes.
[0070] 4. Preparation of material bags: Powders have static electricity, so use a deionizing fan to remove static electricity. Weigh 5.0g of dry powder and put it into the filter. Tie it up with a rope to ensure that the filter does not leak. To ensure that the data is true and valid, prepare two powder bags of the same quality for testing. Accurately weigh the weight of the powder bag and record M1.
[0071] 5. Test: Place the powder bag in the extractor, add 150mL of xylene, test temperature 110℃, extraction times 160±10 times, time 8h.
[0072] 6. Post-processing of material package: After the test, take out the sample, place it in a 75℃ oven, dry it for 8 hours, take out the powder and filter, place it in a dryer, cool it to room temperature, take it out, place it in a room for 15 minutes, weigh it and record the mass M2.
[0073] Comparative Example 1
[0074] Compared with Example 1, after selecting self-produced HP550J polypropylene resin powder, the powder was screened before being spread on a clean glass surface dish, and the particle size selected by screening was 0.3-0.6 mm in diameter, and other conditions remained unchanged.
[0075] Comparative Example 2
[0076] Compared with Example 1, an additional step is added: after the test is completed, the powder bag is rinsed with acetone three times after suction, and purged with nitrogen to evaporate the acetone.
[0077] Comparative Example 3
[0078] Compared with Example 1, the test time of test step 5 is increased to 24 hours.
[0079] The present invention tests the isotacticity of the products prepared in the examples and comparative examples, and the results are shown in Table 1:
[0080] Table 1
[0081]
[0082] It can be seen from the above embodiments that the present invention provides a method for testing the isotacticity of polyolefin materials, comprising the following steps: drying the polyolefin material and placing it in a filter screen, tying it tightly to obtain a powder bag; placing the powder bag in a Soxhlet extractor for extraction, drying the bag to a constant weight after the test is completed, and calculating the isotacticity by subtraction. Compared with traditional detection methods, the detection means described in the present invention has significant advantages in operation. Not only are the steps simple and clear, reducing the difficulty of operation, but the detection results are highly accurate, effectively reducing the error rate. At the same time, the detection method also has a strong timeliness, can quickly feedback the test results, and greatly shortens the product evaluation cycle. Therefore, the present invention can fully meet the strict requirements of polyolefin materials in terms of quality control, product development and market application, and provides strong technical support for the product evaluation of polyolefin materials.
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for testing the isotacticity of a polyolefin material, comprising the following steps: Put the dried polyolefin material into a filter screen and tie it tightly to obtain a powder bag; The powder bag is placed in a Soxhlet extractor for extraction. After the test is completed, the bag is dried to a constant weight, and the isotacticity is calculated by subtraction.
2. The testing method according to claim 1, characterized in that: The holes of the filter screen are 80 mesh, 100 mesh, 120 mesh, 200 mesh, 250 mesh, 300 mesh, 500 mesh, 600 mesh or 800 mesh.
3. The testing method according to claim 1, characterized in that: The polyolefin material is dried at a temperature of 60 to 90° C. and for a time of 1 to 8 hours.
4. The testing method according to claim 1, characterized in that: The extraction temperature is 100-150°C, and the number of extractions is 120-180 times.
5. The testing method according to claim 1, characterized in that: The filter should be dried before use at a temperature of 60 to 90°C for 1 to 8 hours.
6. The testing method according to claim 1, characterized in that: The calculation of isotacticity by subtraction method includes: Measure the total mass of the polyolefin material before extraction, recorded as M1; After extraction and drying to constant weight, measure the mass of the polyolefin sample in the material bag and record it as M2; The calculation formula of isotacticity is: (M1-M2) / M1×100%.
7. The testing method according to claim 1, characterized in that: The polyolefin material to be measured does not need to be screened; There is no need to rinse the samples with acetone after testing.
8. The testing method according to claim 1, characterized in that: The size of the filter is (15-30) cm × (15-30) cm; The shape of the filter is square or rectangular; The width of the binding rope used for tightening is 1 to 3 cm and the length is 10 to 20 cm.
9. The testing method according to claim 1, characterized in that: The solvent used for extraction is selected from xylene, toluene or n-heptane.
10. The testing method according to claim 6, characterized in that: After taking out the sample, place it in an oven at 75±2℃. After drying for 4 to 8 hours, take out the powder and filter and place them in a dryer. After cooling to room temperature, take them out and place them in a room for 15 to 30 minutes. Weigh them and record them as M2.
Citation Information
Patent Citations
Method for detecting mass content of component in polyolefin
CN108254334A
Method for determining gel content in polymer
CN115343187A
Modified polyolefin based on a base polyolefin, which has specific content of propylene and isotactic poly(propylene)-triad and is grafted with silane e.g. vinyltrimethoxy silane, useful as or in molding composition and adhesives
DE102008041281A1
Method for simultaneously measuring content of asphaltene and benzene insoluble substance
WO2024139280A1